(S)-Equol Is More Effective than (R)-Equol in Inhibiting Osteoclast Formation and Enhancing Osteoclast Apoptosis, and Reduces Estrogen Deficiency–Induced Bone Loss in Mice - Tanaka, Miori; Fujii, Shungo; Inoue, Hirofumi; Takahashi, Nobuyuki; Ishimi, Yoshiko; Uehara, Mariko (The Journal of nutrition, 2022)
Equol, a metabolite of daidzein, binds to the estrogen receptor with greater affinity than daidzein and exhibits various biological properties. It exists as an enantiomer, either (S)-equol or (R)-equol. We have previously shown that the inhibitory effect of (S)-equol on bone fragility is stronger than that of racemic equol in ovariectomized (OVX) mice; however, the effect of (R)-equol has not been elucidated. The aim of this study was to compare the activities of equol enantiomers on bone metabolism in vitro and in vivo. Bone marrow cells (BMCs) and RAW 264.7 cells were treated with equol enantiomers. The number of osteoclasts and caspase-3/7 activity were measured. We examined the effect of equol enantiomers on osteoblast differentiation in MC3T3-E1 cells. In vivo, 8-wk-old female ddY mice were assigned to 4 groups: sham-operated (sham), OVX, OVX + 0.5 mg/d of (S)-equol (S-eq), and OVX + 0.5 mg/d of (R)-equol (R-eq). Four weeks after the intervention, femoral bone mineral density (BMD) and osteoclastic gene expression were analyzed, along with concentrations of equol enantiomers in the serum and tissues. (S)-equol and (R)-equol inhibited osteoclast differentiation in BMCs (97% and 60%, P < 0.05) and RAW 264.7 cells (83% and 68%, P < 0.05). (S)-equol promoted apoptosis of mature osteoclasts by inducing caspase-3/7 activity (29%, P < 0.05) and enhanced osteoblast differentiation (29%, P < 0.05). In OVX mice, BMD was ameliorated in (S)-equol-treated mice (11%, P < 0.05), but not in (R)-equol-treated mice. The concentrations of (S)-equol were greater than those of (R)-equol in the serum, tibia, liver, and kidney (by 148%, 80%, 22%, and 139%, respectively). These results suggest that (S)-equol is more effective than (R)-equol in inhibiting osteoclast formation and enhancing osteoclast apoptosis in vitro, supporting the beneficial effect of (S)-equol to reduce estrogen deficiency–induced bone loss in OVX mice.